2008
DOI: 10.1158/1055-9965.epi-08-0058
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Tetrahydrofolate Reductase Genotype Modifies the Chemopreventive Effect of Folate in Colorectal Adenoma, but not Colorectal Cancer

Abstract: Epidemiologic evidence suggests a role for folate, a critical component of the 1-carbon cycle, in colorectal adenoma and cancer pathogenesis. Low folate levels, along with genetic polymorphisms in key enzymes such as methylene tetrahydrofolate reductase (MTHFR), can cause DNA hypomethylation and aberrant CpG methylation, which have been associated with colorectal tumor development. We investigated self-reported folate and alcohol intake alongside possible modifying effects of MTHFR 677 C>T and 1298 A>C polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…Analyses were stratified by sex in some studies, and positive associations with colorectal cancer were reported among men for MTHFR C677T (47) and A1298C (48,50). In addition, similar to our study, the rare T allele of the MTHFR C677T polymorphism has been observed to be associated with increased colorectal cancer risk among women but not among men (48). MTHFR polymorphisms may reduce enzymatic activity and thereby decrease the pool of 5-methyltetrahydrofolate.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Analyses were stratified by sex in some studies, and positive associations with colorectal cancer were reported among men for MTHFR C677T (47) and A1298C (48,50). In addition, similar to our study, the rare T allele of the MTHFR C677T polymorphism has been observed to be associated with increased colorectal cancer risk among women but not among men (48). MTHFR polymorphisms may reduce enzymatic activity and thereby decrease the pool of 5-methyltetrahydrofolate.…”
Section: Discussionsupporting
confidence: 85%
“…Rare variants of these polymorphisms were generally inversely associated with colorectal cancer risk (4,5,12,44,45) or with colorectal adenoma recurrence (46). Conversely, associations with increased colorectal cancer risk (47)(48)(49), colorectal adenoma risk (50), or increased risk for colorectal adenoma recurrence (51,52) have been observed as well. Analyses were stratified by sex in some studies, and positive associations with colorectal cancer were reported among men for MTHFR C677T (47) and A1298C (48,50).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An alternative explanation, suggested in relation to colorectal cancer, 46 relates to differences in circulating folate levels between populations. In the mid to late 1990s fortification of foods with folic acid became mandatory in several countries, including the United States, but not the United Kingdom, resulting in marked increases in folate intake.…”
Section: Discussionmentioning
confidence: 99%
“…Our study show a similar results of the meta-analysis for 11 studies representing over 7,000 case-control study participants published by Deborah et al [17]. In contrast only one reported a significant OR based on gender and genotype Lightfoot and al. found that the men with 677CT genotype had a reduced risk of CRC, and women with 677TT genotype had increased risk [18].…”
Section: Discussionmentioning
confidence: 96%